Green in times of COVID-19: urban green space relevance during the COVID-19 pandemic in Buenos Aires City - Marconi, Patricia Laura (2022)
The COVID-19 pandemic has had a deep impact on the way we perceive our world. This study explores its effect on Urban Green Space (UGS) perception in Buenos Aires City (CABA), Argentina. We provide a detailed overview of the distribution of UGS in CABA, along with socio-economic analysis and visitors' profile and perception before and during the restrictive measures adopted by the national authorities to contain the COVID-19 outbreak (July to December of 2020). We conducted a series of surveys based on open and closed questions. Before the pandemic, surveys were carried out in situ in eight parks of six districts, randomly chosen. During the confinement, online surveys were conducted. According to our results, the mean UGS density in CABA is 6.09 m2 /person, but marked differences between districts exist, ranging from 0.02 m2 /person to 17.68 m2 /person. This uneven distribution causes differences in the quality of life of CABA inhabitants, perhaps more pronounced during reduced-mobility situations like COVID-19 confinement. Socio economic analysis were done linking multidimensional poverty, COVID-19 positive cases and urban mobility in CABA. Regarding UGS visitors, before the confinement, the majority of respondents were employees or students; during the confinement, employees and retirees predominated. When asked to choose important attributes to describe their perception about the UGS from a given list, respondents selected “calm,” “green,” and “sounds of nature,” without differences before and during the confinement. However, when asked about the UGS role, the main answer was “a place to be with nature” before the confinement and “an important place in the city” during it. Understanding how society perceives the UGS, especially during crises, is essential to rethink the urban landscape and prepare our cities, towards biophilic cities and for a more sustainable future.